Compelling overuse injury incidence in youth multisport athletes - Rejeb, A.; Johnson, A.; Vaeyens, R.; Horobeanu, C.; Farooq, A.; Witvrouw, E. (European Journal of Sport Science, 2017)
The present investigation was carried out to examine the incidence and pattern of injuries in adolescent multisport athletes from youth sports academy. Injury data were prospectively collected from 166 athletes during the seasons from 2009 to 2014. A total of 643 injuries were identified, 559 (87.0%) were time-loss injuries. The overall injury incidence was 5.5 (95% confidence interval CI: 5.1-6.0), the incidence of time-loss injuries was 4.8 (95% CI: 4.4-5.2), the incidence of growth conditions was 1.2 (95% CI: 1.0-1.4) and incidence of serious injuries was 0.6 (95% CI: 0.5-0.8) per 1000 h of exposure. The prevalence of overuse injuries was 50.3%. Growth conditions represented 20.0%. Most of the injuries (67.0%) involved the lower extremities, and both foot and ankle were the most predominant injured body parts (22.0%). Knee injuries were mostly from overuse (50 vs. 23, p = .02), whereas foot and ankle injuries resulted from an acute mechanism (94 vs. 31, p < .0001). Minor and moderate injuries accounted for 87.0%. Muscle, tendon and osteochondrosis injuries accounted for 52.0% of all injuries. Comparing groups, squash sport was having the highest injury incidence (8.5 injuries per athlete). Higher exposure was associated with greater overuse relative risk (RR = 1.03, 95% CI: 1.01-1.014, p < .001). In conclusion, the results of this study identified a high incidence of injuries in this youth sports population. Striking was the prevalence of overuse injuries of 50%, which suggests the need for injury prevention protocols for adolescent highly trained athletes.